TATA KELOLA PERUSAHAAN SEBAGAI MEKANISME PENGELOLAAN RISIKO UNTUK MENINGKATKAN NILAI PERUSAHAAN - Edwin Triyuwono; Suwandi Ng; Fransiskus Eduardus Daromes (Media Riset Akuntansi, Auditing & Informasi, 2020)
The aims of the research is to test the effect of corporate governance on firm value mediated by risk. The populations used are listed companies on Indonesia Stock Exchange (IDX) and period of 2013-2018. Purposive sampling is used to determine the sample and secondary data are used in the form of annual and financial reports of the companies. Path analysis and Sobel tests are utilized to test the hypothesis. Research results found that corporate governance has positive and significant effect on risk. Meanwhile, risk has positive and significant effect on firm value. This research also found that risk mediate the effect of corporate governance to firm value. The research implications is to enrich literature of agency theory and stakeholder theory and provide suggestions to companies, investors and the government on the prominence of implementing corporate governance to manage risks for the sustainability of the company which will provide benefits to its stakeholders.